2018
DOI: 10.1167/iovs.17-23003
|View full text |Cite
|
Sign up to set email alerts
|

Composition, Architecture, and Functional Implications of the Connective Tissue Network of the Extraocular Muscles

Abstract: PurposeWe examined the pattern and extent of connective tissue distribution in the extraocular muscles (EOMs) and determined the ability of the interconnected connective tissues to disseminate force laterally.MethodsHuman EOMs were examined for collagens I, III, IV, and VI; fibronectin; laminin; and elastin using immunohistochemistry. Connective tissue distribution was examined with scanning electron microscopy. Rabbit EOMs were examined for levels of force transmission longitudinally and transversely using in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…It is possible that increased myofiber remodeling may result in increased numbers of short myofibers. This would be predicted to result in greater lateral dissipation of muscle force, which is already significant in EOM [ 47 49 ]. It is interesting to note that experimental recession surgery in adult rabbits resulted in a significant increase in myonuclear addition as visualized by bromodeoxyuridine labeling [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that increased myofiber remodeling may result in increased numbers of short myofibers. This would be predicted to result in greater lateral dissipation of muscle force, which is already significant in EOM [ 47 49 ]. It is interesting to note that experimental recession surgery in adult rabbits resulted in a significant increase in myonuclear addition as visualized by bromodeoxyuridine labeling [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, McLoon et al found significant interconnectedness of the connective-tissue elements with all the muscle fibers along the whole length of the muscle, including direct connection into the epimysium, strongly suggesting that individual isolated movements of compartments within the EOM are unlikely. 27 Fat with enveloping connective-tissue sheets keeps the muscle belly in place…”
Section: Direction Of Pull That An Eye Muscle Exerts On the Eyeball Imentioning
confidence: 99%
“…The extraordinary fiber independence reported by Shin et al could be due to epimysium having been stripped off, damaging the connective tissue matrix that normally couples fibers, 36 and to the experimental procedure itself, in which connective tissues joining adjacent fibers were subjected to shear forces far exceeding those they normally sustain. A related study of tendon fiber independence 37 drew a similar, independent critique, complaining that muscle samples had been denuded of ''key surrounding structures'' and subjected to supraphysiologic forces, also citing surgical Z-tenotomy data inconsistent with fiber independence.…”
Section: Mechanical Independence Of Eom Fibersmentioning
confidence: 99%
“…38 If EOMs were composed of parallel independent fibers their total force would be the sum of forces of the individual fibers, which several lines of evidence show is not the case. 33,[39][40][41] McLoon et al 36 showed that epimysium, perimysium, and endomysium of human EOMs form a dense and continuous collagen matrix, with no separations between any muscle regions, limiting relative fiber movements of any kind. Alan B. Scott (personal communication, 2018) sought to selectively ablate OL to weaken primary position forces without impairing eccentric gaze or saccades, but could find no natural laminar cleavage in the horizontal recti of cats, rabbits, or monkeys, even with sharp dissection and laser ablation.…”
Section: Mechanical Independence Of Eom Fibersmentioning
confidence: 99%